Avaliação da produção de pigmentos por microrganismos isolados de painéis fotovoltaicos: otimização do processo, influência da radiação UV e potenciais propriedades biotecnológicas - Oliveira, Juliana Cristina Ramos de (Universidade Federal de São Carlos, 2026)
Microbial pigments represent sustainable alternatives to synthetic dyes. The use of agro-industrial waste as substrates emerges as a promising strategy to reduce costs and increase the viability of the biosynthesis of these metabolites. Microorganisms adapted to extreme environments frequently synthesize pigments as a protective mechanism, making them relevant targets for biotechnological exploration. In this context, the cultivation conditions that favor pigment production by the strains Rhodotorula mucilaginosa PSR 34, Arthrobacter koreensis PSR 37, and Kocuria sp. PSR 51, previously isolated from photovoltaic panels in the city of Sorocaba/SP, an extreme artificial environment of anthropogenic origin, were investigated. Synthetic culture media, soybean molasses as an alternative substrate, incubation time, and temperature were evaluated. Additionally, the influence of UV-A, UV-B, and UV-C radiation on pigment production was determined. Soybean molasses did not prove to be a substrate with superior attributes compared to the use of synthetic media. Determining the ideal conditions revealed differences in the pigment production profile among the analyzed strains. PSR 37 showed the highest production at 15 °C, with 72 hours of incubation, reaching an average concentration of 958.66 µg/L. For PSR 34, the most favorable condition was 15 °C associated with 168 hours of incubation, resulting in 1.66 mg/L of pigment. In contrast, PSR 51 showed the highest production at 30 °C after 72 hours, with an average concentration of 610 µg/L. UV radiation, at the evaluated doses, did not promote an increase in pigment production. Spectral and chromatographic analyses of the PSR 34 pigment indicated the presence of β-carotene and torulene. These pigments demonstrated antimicrobial activity greater than 90% against the tested strains, at a concentration of 7.5 mg/L. Similarly, pigments extracted from PSR 37 and PSR 51 also demonstrated high antimicrobial activity at concentrations of 4.5 and 7.5 mg/L, respectively. All pigment extracts showed a photoprotective factor greater than 30 SPF. The antioxidant activity of the pigments was dependent on exposure time, showing DPPH radical scavenging capacity after 60 minutes of 56.07% for PSR 34, 76.9% for PSR 37, and 89.67% for PSR 51. Furthermore, the pigment extracts exhibited low cytotoxicity in 3T3 and HaCaT cells, maintaining cell viability greater than 50%. These results highlight the promising biotechnological potential of these pigments, reinforcing their relevance for future applications in different industrial sectors.
Evaluation of pigment production by microorganisms isolated from photovoltaic panels: process optimization, influence of UV radiation, and potential biotechnological properties
Keywords: Atividade biológica; Circularidade; Estresse celular; Substrato alternativo; Biological activity; Circularity; Cell stress; Alternative substrate; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; 9. Indústria, Inovação e Infraestrutura